Avaliação de marcadores de estresse oxidativo, inflamatórios e do sistema fibrinolítico em pacientes com fibrilação atrial. - Luana Bernardes Xavier Costa (2022)
Atrial fibrillation (AF) is the most frequent cardiac arrhythmia, and its incidence increases as age advances. The pathology is characterized by irregular electrical activation of the atria, leading to uncoordinated contraction and the formation of atrial thrombi, the main cause of brain stroke and systemic embolism. As the pathophysiology of AF is not yet fully defined, several studies are being carried out evaluating the contribution of oxidative stress and inflammation pathways, as well as fibrinolytic system, in promoting electrical and structural remodeling of the atria, interstitial fibrosis and increased risk of brain stroke. In addition to warfarin, the direct oral anticoagulant, rivaroxaban, a direct activated factor X inhibitor, is currently available for primary and secondary prevention of such events. In this context, the present study aimed to evaluate and compare the association of inflammatory markers, oxidative stress, genetic and fibrinolytic system in individuals with atrial fibrillation, using oral anticoagulants warfarin or rivaroxaban, as well as in a group of control individuals. In blood samples from 147 subjects, including 85 patients with AF (38 on rivaroxan and 47 on warfarin) and 62 control subjects, the parameters of oxidative stress were determined by the dosage of 3-(4,5-Dimethylthiazol-2γl)-2,5-Diphenyl Tetrazoline Bromide (MTT) and thiobarbituric acid reactive substances (TBARS); and the parameters plasminogen activator inhibitor Type 1 (PAI-1), thrombin-activated fibrinolysis inhibitor (TAFI), haptoglobin (Hp) and vitamin D by enzyme immunoassay. The HP genotype was determined using the polymerase chain reaction method. The antioxidant capacity, measure to MTT expression, was significantly elevated in patients using rivaroxaban compared to patients using warfarin and the control group. PAI-1 levels were higher in patients with AF compared to control, but did not differ between control, warfarin and rivaroxaban. TAFI levels were lower in patients with AF, and significantly reduced in patients using rivaroxaban. Serum levels of Hp and vitamin D did not show significant differences between the control, warfarin and rivaroxaban groups. The results found showed the prothrombotic state in the population with arrhythmia. The anticoagulant rivaroxaban may represent a beneficial action by reducing the fibrinolytic inhibitor, in addition to increasing the antioxidant potential.